Administrative practices of foundations in the department of Boyacá: an approach to the administrative reality - Leguizamón Arias, Jimmy Ferney; Ortiz Salamanca, Derly Astrith; Barreto Bernal, Patricia Carolina (Cooperativismo & Desarrollo, 2019)
Introduction: The foundations have taken a representative dimension in the context of the department of Boyacá. However, administrative practices and their management profiles, in contrast to private organizations, are unknown. Methodology: This work explores the concept of foundation as a particular type of NGO, investigating the profiles and administrative practices that are generated around its activity and the contribution that they can make to social innovators in strengthening social management models and organizational structures in this group of non-profit organizations. In-depth interviews and documentary review have been conducted. Results: The findings show the level of evolution of the foundations and administrative practices. Conclusions: The administrative practices identified in the studied foundations contribute elements that improve the management of organizations with the purpose of guaranteeing their sustainability and improving their performance.